Recycling of rare earth particle by mini-hydrocyclones. (March 2017) - Yu, Jian-Feng; Fu, Jian; Cheng, Hao; Cui, Zhengwei
Highlights: The recovery of rare earth particles is realized by mini-hydrocyclone. The influences of feed flow rate, split ratio, feed concentration are investigated. A response surface methodology is applied to obtain the optimum operating parameters. Abstract: Mini-hydrocyclones were applied to separate the fine rare earth particles from the suspensions. The effects of the flow rate, split ratio, and feed concentration on the total separation efficiency and grade separation efficiency were studied. The combined effects of the flow rate (1200–1600 L/h), split ratio (20–60%) and concentration (0.6–1.0 wt%) on the total separation efficiency in mini-hydrocyclones were investigated using a response surface methodology. The optimum operating parameters for a total separation efficiency of 92.5% were: feed flow rate = 1406 L/h, split ratio = 20%, and feed concentration = 1 wt%.